Dream theory from the perspective of Islam - Minoo Asadzandi (International Journal of Psychotherapy Practice and Research, 2018)
Background and Objective: Sleep as a sign of the God wisdom and power, is the agent of stability and tranquility. Sleep has a spiritual dimension. Sincere dreams are the continuation of prophecy and guidance of the God. This study aimed to explain the dream theory from the perspective of Islam. Materials and Methods: This evolutionary study has focused on these questions: “what is the process of dreaming in Islam? Can people control their dreams”? Islamic evidences were taken from the verses and narrations related to the words “soul, sleep, dream and death”, using al-Mu’ayyim, authentic Shi’a commentary books, Bihar al-Anwar, Kofi principles, the Book of Resurrection and life after death. The religious and scientific evidences were analyzed based on the Walker and Event content analysis method. Dream theory was extracted from religious evidence. Results: Based on
Keywords: Islam